Effect of Planting Density and K2O:N Ratio on the Yield, External Quality, and Traders’ Perceived Shelf Life of Pineapple Fruits in Benin - Fassinou-Hotegni, Nicodème V; Lommen, Willemien; HOUNHOUIGAN, DJIDJOHO JOSEPH; Achigan-Dako, Enoch Gbenato; STRUIK, P. C. (My University, 2021)
Quality, shelf life, and yield of a pineapple fruit are the important attributes for the producers and customers in the pineapple value chain of Benin, whereas poor quality, short shelf life, and low yield are themain constraints.We quantified the effects of planting density and K2O:N fertilizer ratio on the pineapple yield, external quality, and perceived shelf life in four on-farm experiments with cv. Sugarloaf in Benin; two experiments were installed in the long rainy season and two in the short rainy season. A split-plot design was used with the planting density as the main factor at three levels: 54,000, 66,600, and 74,000 plants.ha−1. The K2O:N ratio was a subfactor with three levels: K2O:N = 0.35 (farmers’ practice), K2O:N = 1, and K2O:N = 2. The results showed that both factors had no effect on the crop development variables (such as the number of functional leaves and D-leaf length) at the moment of flowering induction. The planting density had no effect on the total weight per fruit, infructescence weight, total fruit length, infructescence length, crown length, or the fruit shelf life as perceived by traders. The yield increased from 54.9– 69.1 up to 90.1 t.ha−1 with an increase in the planting density. The yield increase was not at the expense of the fruit weight. Increased K2O:N ratio led to a higher fruit weight whereas the fruit length was not affected. The shelf life of fruits produced at a K2O:N ratio of 1 and as perceived by traders was 6 days longer than that of fruits produced at a ratio of 0.35 (farmers’ practice). Based on these results, we suggest the fresh pineapple farmers in Benin to use a combination of 66,600 plants.ha−1 with a K-fertilization scheme based on a K2O:N ratio of 1 to meet the expectation of both producers and customers in terms of fruit yield and fruit quality.
Keywords: potassium fertilization; K2O:N ratio; quality attributes; intercropped pineapple; shelf life; planting; density; Benin; Ananas comosus var. comosus